Aplikasi Pengecekan Suhu Dan Penyemprotan Disinfektan Secara Otomatis Berbasis Nodemcu Dengan Telegram - Maulana Malik Ibrahim; Yani Prabowo; Wisjnuadji TW; Yan Everhard; M Anif; Siswanto Siswanto (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2021)
During the current covid-19 pandemic, maintaining health and hygiene is very important for human life, in order to avoid various diseases, such as corona covid-19. One of the protocols imposed by the government is for people who are active in public spaces or open facilities by wearing masks, checking their body temperatures and spraying disinfectants. The problem so far is that there is no automatic disinfectant spraying tool that is very useful for the community during the covid-19 pandemic, in order to reduce appropriate and economical human interaction. detects the presence of humans or objects that are in front of them to become a condition of opening and closing the bars based on the NodeMCU microcontroller with notification and control via telegram messages. Body temperature data will also be displayed on the LCD contained in this tool and sent via telegram to the supervisory officer. Prevention efforts by monitoring body temperature and spraying alcohol-based disinfectants can be applied. The test results of the DS18B20 temperature sensor application can measure human temperature between 370C–390C and the infrared sensor can detect the presence of humans or objects in front of them to open the bars and spray disinfectant